DAKWAH TRANSFORMATIF MOHAMMAD NATSIR - M. Khoirul Hadi al-Asy’ari (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2014)
Da‘wa is probably the best effort to spread Islam. In the context of Indonesia, so many figures engaged in Islamic da‘wa. One of them is Mohammad Natsir who implemented transformative Islamic da‘wa in of his life times. Applying qualitative research with historical approach, both on his life history and his writings, it was found that transformative efforts on the dakwah movement implemented by Mohammad Natsir was based on the principles of verbalic deeds, actualization of Islam in a factual actions, and good personily. The principles had been implemented by doing organizational breakthrough toward the community. Applying this strategy made the da‘wa movement infiltrated toward all levels of society. Nowadays it was showed that the organization set up by Mohammad Natsir developed well and support the religiousity among Indonesian society.